The Terrorist Attack on Utøya Island: long-Term Impact on Survivors’ Health and Implications for Policy - Glad, Kristin Alve (Perspectives on terrorism, 2021)
In this article, we summarize some of the main findings from The Utøya Study, a comprehensive longitudinal study on the impact on the survivors of the July 22 Utøya Island terrorist attack, and describe some implications for future policy. In total, 398 (79%) of the survivors participated in one or more of the four data collections in the study. Their mean age at the time of the terrorist attack was 19.2 years (SD=4.3, range 13.1-56.7, 94.0% < 26 years of age), and 49.0% were female. The vast majority (88.9%) were of Norwegian origin. Participants were interviewed face-to-face at 4-5 months (T1), 14-15 months (T2), 30-32 months (T3), and 8.5 years (T4), post-attack. We found that the terrorist attack had negative repercussions for the survivors’ mental and somatic health for years after the attack, including symptoms of posttraumatic stress, anxiety, depression, complicated grief, headache, and other somatic symptoms. Exposure to the attack also led to long-term functional impairment for many, particularly in relation to the survivors’ academic performance and well-being at school. Furthermore, it had negative health consequences for people close to the survivors, such as their caregivers. An important factor associated with how survivors cope after a terrorist attack is the support and help they receive from their social network, but also from the health care system. In line with the national health outreach plan, most survivors had received early proactive outreach from their municipality, but many missed a broader and longer lasting follow-up. The comprehensive documentation of short- and long-term health and social consequences in this study underlines the challenges societies are faced with after terrorist attacks. This insight calls for actions from decision makers in providing adequate outreach programs in health and social services. In particular, survivors with a non- Norwegian origin reported higher levels of PTSD symptoms and were less satisfied with the follow-up. After future attacks, the official outreach should be proactive, long lasting, and consider the diverse needs and characteristics of the affected individuals. For example, there should be a particular focus on survivors with a minority background. Furthermore, the outreach should be broad, and include people in the survivors’ immediate social network, schools and workplaces.